已知全集U=R,集合A={y|y=-2^x,x∈R},B={y|y=x³-3x,x∈R},则A∩CuB=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 18:52:32
已知全集U=R,集合A={y|y=-2^x,x∈R},B={y|y=x³-3x,x∈R},则A∩CuB=已知全集U=R,集合A={y|y=-2^x,x∈R},B={y|y=x³-3
已知全集U=R,集合A={y|y=-2^x,x∈R},B={y|y=x³-3x,x∈R},则A∩CuB=
已知全集U=R,集合A={y|y=-2^x,x∈R},B={y|y=x³-3x,x∈R},则A∩CuB=
已知全集U=R,集合A={y|y=-2^x,x∈R},B={y|y=x³-3x,x∈R},则A∩CuB=
A={y|y
c是什么东西
得1
已知全集U=R,集合A={y| |y|≤2},集合B={y=2^x},那么A∩(CuB)=
已知全集U=R,集合A={x|-2
已知全集U=R,集合A={X|-2
已知全集U=R,集合A={x|y=根号|2x-1|-3},集合B={x|(x+8)/(x^2+2x+3)
已知全集U=R,集合A=(x/x
已知全集U=R,集合A={x|-1
已知全集U=R,集合A={-1
已知全集U=R,集合A={x|-1
已知全集U=R集合A=1
已知全集U=R,集合A={x|0
已知全集U=R,集合A={x|0
已知全集U=R 集合A={x |-1
已知全集U=R,集合A={x|-7
已知全集U=R,集合A={x|x
已知全集U=R,集合A={x|0
已知全集U=R,集合A={x|x
已知全集U=R,集合A={X|-3
已知全集U=R,集合A={x|0